Physical Implementation of Leaky-Wave Antenna with Engineered Aperture Distribution Based on Bianisotropic Huygens Metasurfaces - Mateos-Ruiz, Pablo; Killamsetty, Vinay Kumar; Epstein, Ariel; Abdo-Sánchez, María Elena (My University, 2023)
A methodology based on omega-type bianisotropic Huygens’ metasurfaces is presented to control the aperture field distribution of leaky-wave antennas. The studied structure is a parallel-plate waveguide with the top plate replaced by a metasurface. Previous works achieved independent control of the phase constant and the leakage factor, but they were constrained to be constant. The required theoretical extensions to overcome this limitation are presented in this work, thus enabling the design of arbitrary radiation patterns. A slowly varying amplitude approximation approach is employed to satisfy Maxwell’s wave equation and obtain the relation between the horizontal and vertical wavenumbers. In addition, a semianalytical algorithm able to predict near-field coupling effects is applied in the microscopic design of the metasurface unit cells. Two designs are carried out with real unit cells, presenting different aperture configurations. Finally, electromagnetic simulations validate the methodology with an excellent agreement without any further full-wave optimization.
Keywords: Antenas; Algoritmos; Ingeniería de control; Telecomunicaciones; Metasurfaces; Antenna; Synthesis algorithm; Leaky-wave; Aperture control; Unit cell design